The Effect of Carob (Ceratonia siliqua) Bean Extract on Semen Parameters and Male Infertility in Human and Animal Experimental Studies: A Systematic Review - Seyyedeh Adeleh Rahmanian; Mahin Kiyani Mask; Fatemeh Sadat Mousavi; Morvarid Irani (Mashhad University of Medical Sciences, 2024)
Introduction: Infertility is a common global problem, approximately 40-50% of which is related to male infertility. Since complementary medications and alternative medicine are recently considered for the treatment of infertility, the current study was conducted with aim to assess the effect of carob on semen parameters and male infertility in human and animal experimental studies. Methods: This systematic review study was performed based on PRISMA guidelines using Persian and English keywords and their possible combinations and search in the following databases: PubMed, Web of Science, Science Direct, Scopus, Medlib, Persian SID and Magiran databases, and Google Scholar search engine with keywords based on MeSh, including siliqua (carob), sperm, testis, male infertility, and semen without time limit until April 2023. The inclusion criteria were human and animal interventional studies conducted on men and male animals. Results: Out of a total of 176 studies, 14 animal studies and three human studies entered the study. The experimental animals included rats, roosters, rams, and dogs. The results of most studies indicated that carob improves sperm parameters such as concentration, progressive motility, morphology, viability, quality, and semen volume. However, the results are contradictory regarding its effect on antioxidant activity, oxidative stress index, and increasing fertility. Conclusion: Carob plant is effective on some parameters of sperm and male fertility, although due to the insufficient number of articles in some cases and the existence of contradictions in the results of some other articles, it is not possible to give a definite opinion about this plant, therefore, to determine its definite effectiveness, it is recommended to design and perform more studies with a larger sample size and a more accurate method.